Hominin Femur finding from Banjarejo: Its morphological character and taxonomical position - Sofwan Noerwidi; Rusyad Adi Suriyanto; Ashwin Prayudi; Harry Widianto (Ikatan Ahli Geologi Indonesia, 2021)
Recently, Banjarejo became an important prehistoric site for Quaternary research because of its significant faunal and hominin remains. This study aims to describe a new finding of the hominin femur specimen from the site and its taxonomical position in human evolution. The specimen was identified by morphological and metric descriptions of the external feature of the femur. Then, comparative study to Homo erectus (n=2), Homo neanderthalensis (n=8), Homo heidelbergensis (n=1), prehistoric Homo sapiens (n=44), Australopithecus africanus (n=1), Paranthropus robustus (n=2), also non-human primate including Pongo (n=1), Macaca (n=1) and Gibbon (n=1) using bivariate and multivariate statistical analysis presented the specimen in the evolutionary perspective. This study shows the morphological and metric character of Banjarejo specimen located between Homo erectus and prehistoric Homo sapiens population sample. Further study should be addressed to investigate the cultural and chronological context of the hominin specimen.